The Alarming Surge of Driving Under the Influence-Related Motor Vehicle Crashes - Al Ma'ani, Mohammad; Castillo Diaz, Francisco; Hejazi, Omar; Khurshid, Muhammad Haris; Kunac, Anastasia; Stewart, Collin; Colosimo, Christina; Nelson, Adam; Magnotti, Louis J.; Joseph, Bellal (The Journal of surgical research, 2025)
The use of alcohol and illicit substances is increasing in the United States. However, it is not clear what proportion of motor vehicle crashes (MVCs) are related to driving under the influence (DUI) of alcohol or drugs. The aim of this study was to assess the prevalence and trends of positive drug and alcohol tests among drivers of MVCs admitted to trauma centers across the United States over the years. This is a retrospective analysis of the American College of Surgeons-Trauma Quality Improvement Program database over 4 years (2017-2020). Using International Classification of Diseases-10 diagnosis and E codes, we included patients presenting after an MVC as a driver of vehicles (cars, motorcycles, heavy transport vehicles, and three-wheeled motor vehicles). Trend analysis was performed for the rates of positive blood or urine toxicology results (alcohol, marijuana, cocaine, amphetamines, methamphetamines, and opiates) among these patients over the years. Over 4 years, from a total of 683,184 MVC drivers with trauma were identified (adolescents [10-19 yr]: 7.6%; young adults [20-64 yr]: 77.1%; older adults [≥65 yr]: 15.3%). The mean (standard deviation) age was 43 (19), and 69% were male. The median (interquartile range) Injury Severity Score was 9 (4-14). The median Glasgow Coma Scale score was 15, and 20% had a Glasgow Coma Scale score of less than 15 on presentation. Overall, 65.8% of the victims were car drivers, followed by motorcyclists (25%), heavy transport vehicle drivers (8.6%), and three-wheeled motor vehicle riders (0.5%). The drug or alcohol screening test was positive in 28.8% of drivers, with 36.3% of them testing positive for more than one substance. Overall, alcohol was the most common substance found (47.1%), followed by marijuana (41.6%), and amphetamines (16.3%). Among those with positive screen tests, 52.9% tested positive for drugs other than alcohol, around two-thirds (59.2%) of which tested positive for marijuana. Trend analysis indicated that the incidence of substance abuse-related MVCs increased significantly from 27% in 2017 to 32% in 2020 (P < 0.001), with the most notable rise in cannabis-abuse-related MVCs (2017:10.2%; 2020:14.6%, P < 0.001). Subanalysis of different age groups demonstrated the same trend toward increasing DUI-related MVCs, with the most prominent rise in the prevalence of marijuana-positive MVC drivers among adolescents. Despite policies in place for the prevention of DUI, the prevalence of drug- or alcohol-related MVCs has been increasing over the years, with over one-third of MVC drivers having a positive drug screen on admission in 2020. This surge was even more prominent among adolescents with positive marijuana screen. These findings provide essential epidemiological data as to the prevalence of DUI, which will further inform policymakers to prevent DUI-related MVCs.